Posterior Reversible Encephalopathy Syndrome Associated with FOLFOX Chemotherapy. (27th February 2013) - Porcello Marrone, Luiz Carlos; Marrone, Bianca Fontana; Pascoal, Tharick Ali; Schilling, Lucas Porcello; Soder, Ricardo Bernardi; Ferreira, Sheila Schuch; Gadonski, Giovani; da Costa, Jaderson Costa
Abstract : Posterior reversible encephalopathy syndrome (PRES) is a clinicoradiologic entity characterized by headaches, altered mental status, seizures, visual loss, and characteristic imaging pattern in brain MRI. The cause of PRES is not yet understood. We report a case of a 27-year-old woman that developed PRES after the use of FOLFOX 5 (oxaliplatin/5-Fluoracil/Leucovorin) chemotherapy for a colorectal cancer.